SPC METHOD OF STATISTICAL CONTROL OF PROCESSES - Khasanov, I. (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In recent decades, the concept of quality has become more and more important. As for the production process, the implementation of quality control allows manufacturing enterprises to develop a high-quality product, which positively affects consumer satisfaction. This article aims to reflect the importance of the method of statistical control of quality processes. In this article, the SPC (Statistical Process Control) method of statistical control of processes, which is one of the effective methods used to prevent inconsistency in technological processes, is explained.